Effect of Moringa oleifera Lam. Leaf Extract on Sperm Motility and Abnormality in White Rats (Rattus norvegicus) Exposed to Cigarette Smoke: An In Vivo Experimental Study - Bachtiar, Harris Yudhanta; Mafruchati, Maslichah; Yudaniayanti, Ira Sari; Restiadi, Tjuk Imam; Utomo, Budi; Plumeriastuti, Hani (Faculty of Veterinary Medicine, Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2025)
Background: CSE has been shown to induce oxidative stress, negatively impacting sperm quality and morphology by decreasing motility and increasing abnormalities. Moringa oleifera Lam. leaves are rich in flavonoids and other antioxidants that may counteract the harmful effects of free radicals. Objectives: This study aimed to investigate the effect of Moringa oleifera leaf extract on sperm motility and abnormality in male white rats (Rattus norvegicus) exposed to cigarette smoke. Method: This true experimental study used a completely randomized design. Twenty-five male rats were divided into five groups: negative control (K−), positive control (K+), and three treatment groups (P1, P2, P3) receiving oral administration of Moringa leaf extract at graded doses (13, 26, and 52 mg/kg BW) for 14 days, along with daily exposure to cigarette smoke. Results: Results showed that group P3 (52 mg/kg BW) had significantly higher sperm motility compared to the positive control and was statistically comparable to the negative control (p<0.05). Furthermore, sperm abnormality in group P3 decreased significantly, approaching the normal range. Conclusion: In conclusion, the administration of Moringa oleifera leaf extract at a dose of 52 mg/kg BW effectively preserved sperm motility and reduced abnormality in white rats exposed to cigarette smoke. These findings support the potential of Moringa oleifera as a phytotherapeutic agent to protect reproductive health against oxidative stress.